2019
DOI: 10.1002/anie.201913024
|View full text |Cite
|
Sign up to set email alerts
|

On‐Surface Synthesis and Characterization of Triply Fused Porphyrin–Graphene Nanoribbon Hybrids

Abstract: On‐surface synthesis offers a versatile approach to prepare novel carbon‐based nanostructures that cannot be obtained by conventional solution chemistry. Graphene nanoribbons (GNRs) have potential for a variety of applications. A key issue for their application in molecular electronics is in the fine‐tuning of their electronic properties through structural modifications, such as heteroatom doping or the incorporation of non‐benzenoid rings. In this context, the covalent fusion of GNRs and porphyrins (Pors) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 58 publications
1
56
0
Order By: Relevance
“…On the other hand, samples with deposited precursors Por(dmp)2 and Por(dmp)4 were annealed above 300 ºC to promote the surface-assisted cyclodehydrogenation between the methyl groups and the macrocycle, giving PorA2 and PorA4, respectively. 63 The corresponding large-scale STM images of PorA2 and PorA4 confirm the presence of individual molecules, but also reveal several side-products, which are tentatively identified as covalently-linked dimers and trimers (Figure 2d,g). High-resolution STM images (Figure 2b,e,h) reveal fully planarized structures with the expected symmetry (i.e., D4h for PorA0 and PorA4, and D2h for PorA2), suggesting the successful formation of the target structures.…”
Section: Synthesis Of Pora0 and Precursors Of Pora2 And Pora4mentioning
confidence: 69%
See 1 more Smart Citation
“…On the other hand, samples with deposited precursors Por(dmp)2 and Por(dmp)4 were annealed above 300 ºC to promote the surface-assisted cyclodehydrogenation between the methyl groups and the macrocycle, giving PorA2 and PorA4, respectively. 63 The corresponding large-scale STM images of PorA2 and PorA4 confirm the presence of individual molecules, but also reveal several side-products, which are tentatively identified as covalently-linked dimers and trimers (Figure 2d,g). High-resolution STM images (Figure 2b,e,h) reveal fully planarized structures with the expected symmetry (i.e., D4h for PorA0 and PorA4, and D2h for PorA2), suggesting the successful formation of the target structures.…”
Section: Synthesis Of Pora0 and Precursors Of Pora2 And Pora4mentioning
confidence: 69%
“…61 On-surface fabrication of π-extended Pors by fusing the macrocycle with PAHs has only recently been reported. 57,62,63 However, the few reported examples involve hybrids of Por with nanographenes, not focusing on the possible open-shell character of the π-system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that p-extended Pors, Por-7AGNR hybrids, and the 7AGNR end states tend to be positively charged by the Au(111) surface. 39,43,44,46 To estimate the effect of possible interactions between the molecule and the underlying substrate, the neutral, monocationic, and dicationic GNR-Por 1(Zn) 2 hybrids were simulated. For the dicationic species, an excellent matching between the simulated LDOS maps and the experimental dI/dV maps was found ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1–3 ] The extension of the chromophores' π‐system represents an efficient tool to alter and therefore tailor the optical properties, e.g., the position of the absorption bands. For that, small polycyclic aromatic hydrocarbons (PAHs) such as benzene [ 4–11 ] or anthracene [ 12–15 ] but also larger ones such as nanographenes [ 16,17 ] or graphene itself [ 18 ] were fused once or several times to porphyrins. Typical synthesis procedures either use already π‐extended pyrrole building blocks for porphyrin synthesis or fuse the desired aromatic units to pre‐formed porphyrins afterwards.…”
Section: Methodsmentioning
confidence: 99%